Numerical analysis and experimental design of a 103 GHz Cherenkov maser - Phipps, A; Maclachlan, A; Robertson, C; Konoplev, I; Phelps, A; Cross, A (IEEE, 2014)
Numerical FDTD and PiC simulations demonstrate the successful electron wave interaction in a Cherenkov maser utilizing a cylindrical 2D PSL as a mode selective cavity. Optimization of this structure's physical properties results in the design of a cavity with 16 longitudinal periods of 1.6 mm length, 7 azimuthal variations and an unperturbed inner radius of 4 mm. In numerical simulations this design produces an output power of 300 kW with 10 % efficiency at a frequency of 103.6 GHz.